INVITED COMMENTARYCAC score vs IVUS MLA: is this the right comparison? - Mintz, Gary S. (Archives of Medical Science, 2009)
Commentary on Prevalence of a minimal luminal cross sectional area of coronary arteries < 4 mm 2 determined by intravascular ultrasound in patients with coronary artery calcium scores of 0-100, 100-200, 200-300, 300-400, and > 400 determined by cardiac computer tomography John H. Shao, Wilbert S. Aronow, Gautham Ravipati, Kumar Kalapatapu, Melvin B. Weiss, Albert J. DeLuca, Craig E. Monsen, Carmen Sorbera, Robert N. Belkin, Anthony L. Pucillo Arch Med Sci 2009; 5, 2: 172–174